Pengaruh Perendaman Gel Lidah Buaya (Aloe Vera) Terhadap Mutu Manisan Lidah Buaya - Ni Made Ari Pradnyani (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Aloe Vera is a plant that grows in Indonesia because of its medicinal functions and can be use in the food industry. The problems that often encountered in the processing of Aloe Vera is the sticky slime on the Aloe Vera gel and has a peculiar smell. The purpose of this research is to know the influence of